Antimicrobial activity of different nanocellulose films embedded with thyme, cinnamon, and oregano essential oils for active packaging application on raspberries - Casalini, Sara (2023)
The study focuses on the antimicrobial activity of nanocellulose films (NFC) embedded with thyme, cinnamon, and oregano essential oils for active packaging application. The activity against model pathogenic bacteria was first tested to obtain each oil's minimum inhibitory concentration (MIC). The tests showed that the surface area of the films and the quantity of essential oil strongly influenced the antimicrobial effect. Then, the different active packaging systems were tested directly on packed raspberries to study their actual commercial packaging conditions. Through 12 days of storage at 1 & DEG;C, it was observed that thyme and oregano essential oils were more effective in maintaining the firmness and reducing the weight loss of the fruits compared to cinnamon essential oil or the control; no significant effect was observed on the other quality parameters that were considered. The essential oils independently proved effective in preventing fungal growth. However, the combined impact of thyme+oregano (NAP_TO) demonstrated the best performance.